2020
DOI: 10.4236/aces.2020.101003
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquids and Deep Eutectic Solvents and Their Use for Dissolving Animal Hair

Abstract: In recent years, one of the priority areas of research in chemistry has become the processes carried out in an environment of liquid organic salts, the so-called ionic liquids (ILs), which are assessed as environmentally friendly or "green" alternatives to conventional organic solvents. ILs are non-volatile, highly polar solvents that dissolve many organic, inorganic, and organometallic compounds. Since they have no detectable vapor pressure, ILs are considered as potential substitutes for volatile organic com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The molecular weight obtained for keratin was ranging from 3.8 to 5.8 kDa, comparable to the conventional methods [ 67 ]. In another study, Sakhno et al [ 102 ] measured the solubility of rabbit hair in a mixture of two DES in a different composition. DES 1 consisted of a combination of choline chloride and urea and DES 2 in a combination of choline chloride and urea-hydrogen peroxide adduct both with the molar ratio of 1:2.…”
Section: Methods For the Valorization Of Keratins By Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular weight obtained for keratin was ranging from 3.8 to 5.8 kDa, comparable to the conventional methods [ 67 ]. In another study, Sakhno et al [ 102 ] measured the solubility of rabbit hair in a mixture of two DES in a different composition. DES 1 consisted of a combination of choline chloride and urea and DES 2 in a combination of choline chloride and urea-hydrogen peroxide adduct both with the molar ratio of 1:2.…”
Section: Methods For the Valorization Of Keratins By Extractionmentioning
confidence: 99%
“…The extraction was carried out for 10 h at a temperature of 30 °C. Results showed that the mixture of DES 1 and DES 2 (1:2) had the highest solubility (79%) for the rabbit hair [ 102 ].…”
Section: Methods For the Valorization Of Keratins By Extractionmentioning
confidence: 99%
“…[28] The ability of DESs to disturb the hydrogen bonding and electrostatic bonds present in wool enhances the dissolution of keratin [16,29,30]. This also results in the formation of random coil and β-sheet structures [4].…”
Section: The Solubility Of Wool Keratin In Des and Extraction Yieldsmentioning
confidence: 99%
“…The main physicochemical methods of keratin treatment are solubilization in organic solvents or ionic liquids, hydrothermal treatment, acid or alkaline hydrolysis, oxidation or reduction in disulfide bridges by the addition of chemicals, and degradation of hydrogen bonds, e.g., by urea [ 23 , 24 , 31 , 32 , 33 ]. The choice of the treatment method has a significant impact on the composition of the extracted keratin and keratin hydrolysate and largely depends on the intended future use of the final product [ 30 , 31 , 34 , 35 , 36 ]. A comparison of various physicochemical treatment methods with their advantages and disadvantages are presented in Table 2 .…”
Section: Conventional Keratin Degradationmentioning
confidence: 99%